Diagnosing the Philippine economy toward inclusive growth - Canlas, Dante B.; Khan, Muhammad Ehsan; Zhuang, Juzhong. (The Anthem-Asian Development Bank Series, 2009)
'Diagnosing the Philippine Economy' describes the conditions that depress economic growth in the Philippine economy and their causes and potential solutions.